Artificial intelligence and symbolic computation : 13th International Conference, AISC 2018, Suzhou, China, September 16-19, 2018, Proceedings /: 13th International Conference, AISC 2018, Suzhou, China, September 16-19, 2018, Proceedings. (2018) - Unknown
No abstract available